2022
DOI: 10.1097/shk.0000000000001985
|View full text |Cite
|
Sign up to set email alerts
|

A2A Adenosine Receptors Regulate Multiple Organ Failure After Hemorrhagic Shock in Mice

Abstract: Trauma hemorrhagic shock (T/HS) is a clinical condition that causes multiple organ failure that needs rapid intervention. Restricted oxygen at the cellular level causes inflammation and subsequent cell death. Adenosine triphosphate is the universal intracellular energy currency and an important extracellular inflammatory signaling molecule. Adenosine, an endogenous nucleotide formed as a result of the breakdown of adenosine triphosphate, is also released during T/HS. Adenosine binds to four G protein–coupled r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 73 publications
(88 reference statements)
0
12
0
Order By: Relevance
“…The ability to block A2aR to improve survival in a CLP model of sepsis has been reported widely (13,14,41). As in previous studies, we found that the blockade of A2aR improved survival and suppressed Foxp3 expression (14).…”
Section: Discussionmentioning
confidence: 99%
“…The ability to block A2aR to improve survival in a CLP model of sepsis has been reported widely (13,14,41). As in previous studies, we found that the blockade of A2aR improved survival and suppressed Foxp3 expression (14).…”
Section: Discussionmentioning
confidence: 99%
“…The mice were given anesthesia using 1% isoflurane and their rectal temperature was maintained between 36.5 and 37.5 °C using a feedback-controlled homeothermic blanket heating system (Sumno-suite, Kent Scientific). Hemorrhagic shock was induced using a fixed-pressure model [ 34 ] as described in the Additional data. Initially, a midline laparotomy of 2 cm was performed on the anesthetized mice, which was later closed with a 4 − 0 silk suture (034902, Covetrus, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, after a small incision a syringe with a 23G needle filled with 1 ml of sterile saline was inserted into the trachea. After centrifugation (1500 x g for 15 min at 4 °C) the supernatant was used for the assays [ 34 ]. ATP (ab83355, Abcam, USA) and cAMP (KGE012B, R&D Systems, USA) in BALF were measured by a colorimetric assay.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations